2018
DOI: 10.1080/19336950.2018.1511512
|View full text |Cite
|
Sign up to set email alerts
|

Lack of correlation between surface expression and currents in epileptogenic AB-calmodulin binding domain Kv7.2 potassium channel mutants

Abstract: Heteromers of Kv7.2/Kv7.3 subunits constitute the main substrate of the neuronal M-current that limits neuronal hyper-excitability and firing frequency. Calmodulin (CaM) binding is essential for surface expression of Kv7 channels, and disruption of this interaction leads to diseases ranging from mild epilepsy to early onset encephalopathy. In this study, we addressed the impact of a charge neutralizing mutation located at the periphery of helix B (K526N). We found that, CaM binding and surface expression was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…CaM was reported to be an auxiliary subunit of Kv7 channels (Wen and Levitan, 2002). Disrupted CaM interactions with Kv7 channels have been shown to be tightly associated with severely impaired Kv7 surface expression (Ghosh et al, 2006;Shamgar et al, 2006;Etxeberria et al, 2008;Alaimo et al, 2009Alaimo et al, , 2018Liu and Devaux, 2014;Chang et al, 2018), illustrating the vital role of CaM in Kv7 assembly and trafficking, which is also supported by our study. Additionally, the stoichiometry for CaM binding to the Kv7 subunit was 1:1 (Sun andMacKinnon, 2017), andBernardo-Seisdedos et al (2018) reported that the Kv7.2 A and B helices could not be purified in the absence of CaM and that the complex could not be dissociated at any calcium concentration in vitro.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…CaM was reported to be an auxiliary subunit of Kv7 channels (Wen and Levitan, 2002). Disrupted CaM interactions with Kv7 channels have been shown to be tightly associated with severely impaired Kv7 surface expression (Ghosh et al, 2006;Shamgar et al, 2006;Etxeberria et al, 2008;Alaimo et al, 2009Alaimo et al, , 2018Liu and Devaux, 2014;Chang et al, 2018), illustrating the vital role of CaM in Kv7 assembly and trafficking, which is also supported by our study. Additionally, the stoichiometry for CaM binding to the Kv7 subunit was 1:1 (Sun andMacKinnon, 2017), andBernardo-Seisdedos et al (2018) reported that the Kv7.2 A and B helices could not be purified in the absence of CaM and that the complex could not be dissociated at any calcium concentration in vitro.…”
Section: Discussionsupporting
confidence: 88%
“…Earlier studies mostly focused on the role of the C-terminal domain of Kv7 channels in CaM binding and CaM regulation. Mutations in the C-terminal domain impairing CaM binding affect channel assembly, trafficking, and gating (Ghosh et al, 2006;Shamgar et al, 2006;Etxeberria et al, 2008;Alaimo et al, 2009Alaimo et al, , 2018Liu and Devaux, 2014;Tobelaim et al, 2017;Chang et al, 2018). Here, our data provided new insight into CaM regulation of Kv7 channels by proving that the S2-S3 loop of Kv7.4 channels is essential for CaM-mediated calcium-dependent regulation of Kv7.4 activation.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…There are contrasting reports regarding the effect of the K526N (K554N in isoform 1) mutation on CaM binding, voltage-dependence, and membrane surface expression (Table 4; Figure 3). There is general agreement on an impact on PIP 2 sensitivity and a tendency to increase current density [105,106,113]. Similar to other mutations at or close to the CaM binding surface, channels carrying this mutation are less efficient at controlling neuronal excitability [106].…”
Section: Neuronal Channelsmentioning
confidence: 98%
“…Whereas the R333W mutant interferes with CaM binding, the R333Q mutation does not. However, both mutations affect channel trafficking [105,106] (Table 4; Figure 3).…”
Section: Neuronal Channelsmentioning
confidence: 99%